Word play : a cornucopia of puns, anagrams, euphemisms & other contortions & curiosities of the English language /: a cornucopia of puns, anagrams, euphemisms & other contortions & curiosities of the English language. (2015) - Brandreth, Gyles Daubeney, 1948-
No abstract available